A new myrmecophilous mite species of the genus Cosmolaelaps Berlese, 1903 (Acari, Mesostigmata, Laelapidae) from Central Europe (Slovakia) - Mašán, Peter; Babaeian, Esmaeil (Zootaxa, 2019)
A new laelapid mite of the genus Cosmolaelaps Berlese, 1903, C. ekaterinae sp. n., is described based on female and male adults found in a mixed ant colony of Lasius umbratus (Nylander, 1846) infiltrated by another congeneric species, Lasius fuliginosus (Latreille, 1798). The new species is unusual for Cosmolaelaps in having dorsal setae that are particularly elongate and tapered. In addition to the new species description, we comment on the classification of some species that were recently included in Cosmolaelaps.